Satysfakcja zawodowa a style humoru nauczycieli - Karłyk-Ćwik, Anna (Studia Edukacyjne, 2020)
Karłyk-Ćwik Anna, Satysfakcja zawodowa a style humoru nauczycieli [Job Satisfaction and Teachers’ Humor Styles]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 129-152. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.7 The article contains a presentation of the results of empirical research, which purpose was to diagnose the general level of teachers’ job satisfaction and its disaggregation depending on gender, age and seniority, and to diagnose styles of humor presented by teachers, as well as to determine the relationship between these variables. The research sample was a group of 113 teachers from 11 randomly selected middle schools from Western Poland. A survey revealed no differentiation of professional satisfaction on the part of the teachers surveyed in terms of sex, age and length of employment. However, it was revealed that self-enhancing humor, relatively weak, but statistically significant (r = 0.289), correlates positively with the level of teachers’ professional satisfaction. The results confirm the assumption that this kind of adaptive humor is an individual factor that holds an important role in increasing a sense of satisfaction and well-being of individuals.